HUBUNGAN ANTARA MOTIVASI BELAJAR DENGAN HASIL BELAJAR SISWA MATA PELAJARAN IPA KELAS IV DI SD NEGERI 3 MLANDINGAN WETAN TAHUN PELAJARAN 2016/2017 - Lailatur Rofi’a; Dodik Eko Yulianto (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Abdurachman Saleh Situbondo, 2017)
This research was conducted in clas 4 SDN 3 Mlandingan Wetan country districts Bungatan 20 students. Studies determining the corelation between learning motivation and learning out comes to IPA subject in clas 4 SDN 3 Mlandingan Wetan this research is Quantitative research, questionnaire held on december 7 to 22 august 2016 while date analysis is used to test the validity, realibility test, and test product moment correlation. From date analysis, it can be concluded that there is a relationship beetwen learning motivation and learning out comes of students in clas 4 IPA subject in SDN 3 Mlandingan Wetan. This show that student who have high motivation so it will have a high learning outcomes and o if the low learning moivation, so the learning outcomes will be low